The oxford handbook of management in emerging markets - Grosse, Robert; Meyer, Klaus E. (New York Oxford University Press, 2019)
Emerging Markets are the primary source of growth for business in the 21st century. This makes an understanding of managing businesses in emerging markets a fundamental building block for competing in today's global economy. This book's approach is to identify key elements of the business systems and competition in emerging markets around the world, and then to look at competitive strategies of local and multinational companies going into and coming out of these countries.